The Impact of Learning Organization on Organizational Innovation with Self-Efficacy and Knowledge Management as Mediators - Sri Rahayuningsih; Kusuma Chandra Kirana; Syamsul Hadi (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
This study seeks to explore the impact of Learning Organization on Organizational Innovation, with Knowledge Management and Self-Efficacy examined as mediating variables, focusing specifically on university lecturers in Indonesia. Adopting a quantitative approach, the research utilized a survey method to collect data from 178 participants, selected using the Slovin formula. Data was collected using structured questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Learning Organization has a strong and positive effect on Organizational Innovation, both directly and indirectly. Notably, Knowledge Management serves as a partial mediator, enhancing the link between Learning Organization and innovation outcomes. In contrast, Self-Efficacy did not show a statistically significant mediating effect. These findings highlight the critical role of cultivating an organizational culture that promotes ongoing learning and the strategic application of knowledge management practices to foster long-term innovation. The study provides important insights for higher education institutions, particularly in enhancing organizational learning, refining knowledge management systems, and designing initiatives that promote innovation-driven environments.